Studi Eksperimental Formulasi Infused Water Kurma Jeruk Nipis terhadap Aktivitas Antioksidan dan Kesukaan - Salsabila, Uyun; Ambarwati, Ria; Muninggar , Dian; Isnawati, Muflihah; Yuniarti (Program Studi Gizi, Universitas Bumigora, 2025)
Infused water is developed as a functional beverage alternative containing natural antioxidants. The combination of dates and lime in infused water can enhance phenol levels and antioxidant activity. This study aimed to examine the effect of adding lime to date-infused water on total phenolic content, antioxidant activity, and consumer preference. The research employed an experimental method with a Completely Randomized Design (CRD), involving two replications of three formulations. The treatments: F1 (45 grams of dates: 10 grams of lime), F2 (45 grams of dates: 20 grams of lime), and F3 (45 grams of dates: 30 grams of lime). The infused water was soaked for 12 hours at 4°C in a chiller. Total phenol content was measured using the Folin-Ciocalteu method with a UV-Vis spectrophotometer, while antioxidant activity was tested using the DPPH method. A hedonic test was conducted with 25 semi-trained panelists. Data were analyzed using a normality test, ANOVA, and Duncan’s post hoc test. The results showed that the addition of lime significantly increased the total phenol content and antioxidant activity (p-value = 0.0001). F3 had the highest phenol content (244.34 mg GAE/ml) and antioxidant activity (IC50 = 57.94 ppm), while F2 was the most preferred. In conclusion, lime addition influenced the functional and sensory qualities of date-infused water.